TE-greedy-nester: structure-based detection of LTR retrotransposons and their nesting - Lexa, Matej; Jedlicka, Pavel; Vanat, Ivan; Cervenansky, Michal; Kejnovsky, Eduard (Bioinformatics, 2020)
MOTIVATION: Transposable elements (TEs) in eukaryotes often get inserted into one another, forming sequences that become a complex mixture of full-length elements and their fragments. The reconstruction of full-length elements and the order in which they have been inserted is important for genome and transposon evolution studies. However, the accumulation of mutations and genome rearrangements over evolutionary time makes this process error-prone and decreases the efficiency of software aiming to recover all nested full-length TEs. RESULTS: We created software that uses a greedy recursive algorithm to mine increasingly fragmented copies of full-length LTR retrotransposons in assembled genomes and other sequence data. The software called TE-greedy-nester considers not only sequence similarity but also the structure of elements. This new tool was tested on a set of natural and synthetic sequences and its accuracy was compared to similar software. We found TE-greedy-nester to be superior in a number of parameters, namely computation time and full-length TE recovery in highly nested regions. AVAILABILITY AND IMPLEMENTATION: http://gitlab.fi.muni.cz/lexa/nested. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: algoritmy; Software; Retroelements; Evolution, Molecular; retroelementy; Algorithms; transpozibilní elementy DNA; software; molekulární evoluce; DNA Transposable Elements